The transition to flowering in winter rapeseed during vernalization. (23rd November 2020) - Matar, Sarah; Kumar, Avneesh; Holtgräwe, Daniela; Weisshaar, Bernd; Melzer, Siegbert
Abstract: Flowering time is a major determinant of adaptation, fitness and yield in the allopolyploid species rapeseed ( Brassica napus ). Despite being a close relative to Arabidopsis thaliana, little is known about the timing of floral transition and the genes that govern this process. Winter, semi‐winter and spring type plants have important life history characteristics that differ in vernalization requirements for flowering and are important for growing rapeseed in different regions of the world. In this study, we investigated the timing of vernalization‐driven floral transition in winter rapeseed and the effect of photoperiod and developmental age on flowering time and vernalization responsiveness. Microscopy and whole transcriptome analyses at the shoot apical meristems of plants grown under controlled conditions showed that floral transition is initiated within few weeks of vernalization. Certain Bna.SOC1 and Bna.SPL5 homeologs were among the induced genes, suggesting that they are regulating the timing of cold‐induced floral transition. Moreover, the flowering response of plants with shorter pre‐vernalization period correlated with a delayed expression of Bna.SOC1 and Bna.SPL5 genes. In essence, this study presents a detailed analysis of vernalization‐driven floral transition and the aspects of juvenility and dormancy and their effect on flowering time in rapeseed. Abstract : In the field, winter rapeseed plants produced floral buds after a short period of cold, however, flowering was delayed by several months. Microscopic and transcriptomic studies at the shoot apical meristems of plants grown under controlled conditions confirmed the initiation of floral transition within few weeks of vernalization. Specific gene homeologs were up‐regulated during vernalization, suggesting that they play a role in cold‐induced floral induction.